Monocharged electret based liquid-solid interacting triboelectric nanogenerator for its boosted electrical output performance. (April 2020) - Jang, Sunmin; La, Moonwoo; Cho, Sumin; Yun, Yeongcheol; Choi, Jun Hyuk; Ra, Yoonsang; Park, Sung Jea; Choi, Dongwhi
Abstract: Among various energy harvesters to effectively use the renewable clean energy sources, the triboelectric nanogenerator (TENG) is in the spotlight due to its advantages of material and processing diversity. Especially, the novel TENG utilizing an interaction of moving liquid on the hydrophobic solid surface instead of a solid-solid interaction, called liquid-solid interacting TENG (L-S TENG), is regarded as a promising platform for harvesting ubiquitous liquid-solid contact and separation such as an ocean wave or a falling rainwater. However, the electrical output performance from the L-S TENG is too low to be practically utilized as a power source in our daily lives and further, the L-S TENG has demonstrated an issue in its output degradation with ions containing aqueous solutions. In this study, instead of introducing microscale or nanoscale surface topography on the L-S TENG to enhance the triboelectricity, the strategy to improve induction of electrical charges during its operation is proposed to amazingly enhance its output performance. More than 1000 times increase of peak power with high flexibility and high light transmittance (~92%) can be easily achieved by artificially injecting the electrical charges on amorphous fluoropolymer. The proposed strategy shows the possibility to generate more than 80 V with seawater-like electrolyte solution without application of cumbersome and complicated processes. In this regard, this study would broaden the applicability of the L-S TENG by effectively overcoming one of the fatal drawbacks of the L-S TENG and eventually, it would enable practical use of the L-S TENG such as blue energy harvesting. Graphical abstract: Image 1 Highlights: Significant increase of electrical output of liquid-solid triboelectric nanogenerator (L-S TENG). Emphasize importance of improving electrical charge induction during operation of (L-S TENG). Highly transparent and flexible L-S TENG with enhanced performance. Generation of tens of volts by using a drop of high amount ions containing aqueous solution.